Invented Tradition in Anton Webern’s String Trio, Op. 20 - Catherine Nolan (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2014)
Webern’s String Trio, Op. 20, completed in 1927, marks his return to instrumental composition after over a decade of vocal writing (from Op. 12 to Op. 19), and also demonstrates his technical mastery of the twelve-tone method with which he had been experimenting during the preceding few years. In the absence of a text, Webern’s compositional procedures adapted to the instrumental medium, and the two movements of the String Trio reveal formal designs deeply reminiscent of the traditions of tonal instrumental music. This essay examines the String Trio, particularly its first movement, using the trope of “invented tradition” articulated by historian Eric Hobsbawm, in order to show that those formal traditions are not simply followed, but are transformed through radically new twelve-tone relations. The symbolic function of tradition, not mere convention, provides an orderly outline within which Webern developed new discursive practices that became part of his unique twelve-tone language. Invented tradition in the context of the String Trio not only offers insights into Webern’s new discursive practices, but also into the multifaceted nature of musical modernism. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part V).